2001
DOI: 10.1001/jama.286.17.2136
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Myeloperoxidase Levels and Risk of Coronary Artery Disease

Abstract: Elevated levels of leukocyte- and blood-MPO are associated with the presence of CAD. These findings support a potential role for MPO as an inflammatory marker in CAD and may have implications for atherosclerosis diagnosis and risk assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
530
5
18

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 832 publications
(570 citation statements)
references
References 52 publications
17
530
5
18
Order By: Relevance
“…Accordingly, MRS sensors for myelperoxidase (MPO), an enzyme associated with atherosclerosis and inflammation, 162 were designed as serotonin-labeled SPIO which become cross-linked in the presence of MPO. 107 Although not validated in vivo, these probes certainly take the first steps toward extending MRS-based probes into living subjects.…”
Section: Protein and Enzyme Detectionmentioning
confidence: 99%
“…Accordingly, MRS sensors for myelperoxidase (MPO), an enzyme associated with atherosclerosis and inflammation, 162 were designed as serotonin-labeled SPIO which become cross-linked in the presence of MPO. 107 Although not validated in vivo, these probes certainly take the first steps toward extending MRS-based probes into living subjects.…”
Section: Protein and Enzyme Detectionmentioning
confidence: 99%
“…18,38,39 Because rotenone exposure caused a notable increase in MPO expression, we sought to determine whether MPO could influence the ability of microglia to mediate cellular events in the rotenone-exposed brain. First, we investigated the effects of MPO on the viability of microglia.…”
Section: Mpo Enhances Production Of Ros and Inflammation-associated Mmentioning
confidence: 99%
“…MPO, released from activated leucocytes, catalyses the formation of HOCl from physiological concentrations of Cl − ions and H # O # (generated via the oxidative burst of leucocytes as well as other cells) [29]. It has been shown that both active MPO, and the products of its action, are present in various grades of human atherosclerotic lesion [22,24,30], and that the levels of this enzyme are strongly associated with coronary artery disease [31][32][33].…”
Section: Introductionmentioning
confidence: 99%